Role of Stock Market to Develop Financial Literacy in Rural Area of Nepal - Bhandari, Subash Chandra (Innovative Research Journal, 2026)
By analyzing the crucial role local share markets play in promoting financial literacy across the nation. This study addresses the persistent discrepancy in financial education and inclusion in Nepal. Using a mixed-methods approach that incorporates surveys of 100 retail investors and interviews with financial educators a rural area, the study examines how participation in local share trading enhances understanding of financial concepts, risk management, and investing principles. Active involvement in Nepal’s stock market significantly increases financial literacy levels, as evidenced by the fact that 68% of participants demonstrated enhanced comprehension of financial concepts, market dynamics, and economic indicators after a year of trading. Local share investment offers a practical learning environment, especially in urban and semi-urban areas where standard banking services are still hard to come by. Inadequate investor education programs, a lack of resources in the vernacular, and insufficient regulatory frameworks safeguarding rookie investors are some of the major issues that the study highlights. According to the study, financial literacy training should be required through NEPSE, localized educational materials should be developed, and investor protection measures should be implemented. These findings suggest that increasing national financial literacy rates can be accomplished through democratized access to capital markets, which has significant implications for policymakers seeking to enhance financial inclusion and economic participation.